2017
DOI: 10.3390/nu9101070
|View full text |Cite
|
Sign up to set email alerts
|

Cynanchum wilfordii Ameliorates Testosterone-Induced Benign Prostatic Hyperplasia by Regulating 5α-Reductase and Androgen Receptor Activities in a Rat Model

Abstract: Benign prostatic hyperplasia (BPH) is characterized by uncontrolled proliferation of the prostate gland. Cynanchum wilfordii has been reported to improve sexual behavior in male rats. In this study, we investigated the protective effect of an aqueous extract of C. wilfordii (CWW) against BPH development in a testosterone-induced BPH rat model. The rats were divided into the following six groups: sham/vehicle; BPH/vehicle; BPH/finasteride; and three CWW doses (50, 100, and 200 mg/kg). After a 4-week treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
0
25
1
Order By: Relevance
“…In particular, there are no consistent reports on whether significant proliferation in the prostatic stroma is observed. For example, some studies reported stromal lesions [ 11 , 12 , 24 ], whereas others only reported epithelial lesions [ 10 , 13 , 25 28 ]. Taken together, the traditional method of hormone-induced model has some limitations in the study of BPH-related mechanism and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are no consistent reports on whether significant proliferation in the prostatic stroma is observed. For example, some studies reported stromal lesions [ 11 , 12 , 24 ], whereas others only reported epithelial lesions [ 10 , 13 , 25 28 ]. Taken together, the traditional method of hormone-induced model has some limitations in the study of BPH-related mechanism and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another important biomarker for the diagnosis of BPH is serum prostate specific antigen (PSA) levels. PSA is a serine protease glycoprotein which is naturally produced by epithelial cells of the prostate, and it is produced in minute amounts in the serum, but seen to be greatly elevated in BPH and prostate cancer [29]. Reduction of serum PSA levels is, therefore, indicative of the effectiveness of a trial drug or natural agent in the treatment of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of CWW (200 mg/kg/d for 7 days, per os) significantly improves skin temperature increase in OVX rats [ 119 ]. Moreover, the aqueous extract of CWW inhibits the development of benign prostatic hyperplasia (BPH) in a testosterone-induced BPH rat model [ 120 ]. In addition, compound 22 showed an airway smooth muscle relaxant effect [ 12 ].…”
Section: Pharmacologymentioning
confidence: 99%